2013
DOI: 10.1590/s0102-86502013000300003
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning attenuates remote pulmonary inflammatory infiltration of diabetic rats with an intestinal and hepatic ischemia-reperfusion injury

Abstract: PURPOSE:To assess ischemic preconditioning (IPC) effects in pulmonary lesion in intestinal and hepatic ischemia-reperfusion (IR) injury models using diabetic rats.METHODS: Diabetes (DM) was induced in 28 male Wistar rats by alloxan (42 mg/kg, IV). After 28 days, severe DM rats were submitted to intestinal or hepatic IR injury with or without IPC. Intestinal IR (30 min of mesenteric artery occlusion and 30 min of reperfusion; n=6) and IPC groups (10 min ischemia, 10 min reperfusion, followed by intestinal IR; n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…Inflammatory answer is an important factor to the exacerbation of I/R injury and uncontrolled inflammation and advanced tissue damage [ 44 ]. I/R injury induces to the translocation of toxins and bacteria, leading to systemic inflammation and in the occurrence of MODS and SIRS.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory answer is an important factor to the exacerbation of I/R injury and uncontrolled inflammation and advanced tissue damage [ 44 ]. I/R injury induces to the translocation of toxins and bacteria, leading to systemic inflammation and in the occurrence of MODS and SIRS.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation is another important contributor to the exacerbation of IRI 18 , and we detected IL-6 and TNF-α as markers of the inflammatory response 20 . The role of montelukast to reduce IL-6 and TNF-α has not been previously reported in intestinal IRI.…”
Section: Discussionmentioning
confidence: 74%
“…Intestinal IRI is a troublesome clinical disease with a high mortality rate, despite surgical intervention 17 . Ischemia and reperfusion injury has different pathophysiological features with the major mucosal injury happening during the reperfusion phase 18 19 . Thus, using pharmacological agents is an important strategy for preventing intestinal ischemic injury during intestinal IRI 19 20 21 22 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thomaz Neto et al [ 21 ] had already shown that the mesenteric I/R process causes mild lung injury, and that this can be minimized by ischemic preconditioning. However, this method of prevention has limited clinical applicability, since the identifying mesenteric ischemia no further opportunity for their use.…”
Section: Discussionmentioning
confidence: 99%